A Twitter-facilitated professional learning community: online participation, connectedness, and satisfaction - Binbin Zheng; Gary Beck Dallaghan (BMC Medical Education, 2022)
Abstract Background Twitter has gained increasing popularity and attention as a professional learning environment to share knowledge, exchange information, make connections, and build networks. To evaluate the effectiveness of Twitter-facilitated online discussions, a community of inquiry framework could be used with the three key elements of online environments: cognitive presence, social presence, and teaching presence. This study aims to explore how medical educators participate in synchronous online discussions on Twitter using #MedEdChat, and how participants’ perceptions toward the three presences, sense of connectedness and interactions influenced their online satisfaction. Methods A survey invitation was emailed using the medical education email list DR-ED and was posted during the weekly Twitter conversations in December 2020, to solicit participants who have been involved in any kind of #MedEdChat activities (i.e., read transcripts or directly participate in discussions). Results A total of 68 people responded. Through descriptive analysis and path analysis, we found that almost half of the survey respondents were lurkers on #MedEdChat who read others’ tweets or transcripts. In addition, participants mainly used Twitter for resource sharing, collaborating with others, and networking. Participants rated teaching (i.e., moderator) presence the highest, followed by overall satisfaction, cognitive presence, sense of connectedness, social presence, and interactions. Among them, sense of connectedness and cognitive presence were significantly associated with participants’ overall satisfaction. Conclusions This study provided significant implications for using Twitter as a professional learning community to conduct online discussion activities. Facilitators could think of ways to improve participation by providing tutorials on how to participate on Twitter discussions, introduce or ask new participants to introduce themselves, facilitate discussion with intriguing questions, and invite medical educators of different roles as well as medical students and residents to join to bring in diverse perspectives.